DSSAT Nitrogen Cycle Simulation of Cover Crop–Maize Rotations under Irrigated Mediterranean Conditions. (1st July 2014) - Salmerón, Montserrat; Cavero, José; Isla, Ramón; Porter, Cheryl H.; Jones, James W.; Boote, Kenneth J.
Abstract : The accurate simulation of N cycle in winter cover crop–maize rotations can help to study management practices aimed at reducing N leaching. A lysimeter and field experiment were used to calibrate and test the model under irrigated Mediterranean conditions. Thereafter, the model was used to evaluate the impact of cover crop–maize rotations on N leaching for a range of soil types and irrigation managements during a 14 yr rotation in La Violada watershed, Spain. The Decision Support System for Agrotechnology Transfer (DSSAT) v4.5.0.51 soil temperature subroutine overpredicted soil temperature, but this was improved when using a new EPIC‐based soil temperature subroutine that will be available in DSSAT v4.6. The model was accurate simulating total maize N content in maize after fallow and after different cover crops (root mean square error [RMSE] = 25 kg N ha −1 ), adequately simulated N leaching reductions with cover crops, and was less efficient simulating soil inorganic N. Overall, the DSSAT‐CENTURY model proved appropriate to simulate N cycle. DSSAT‐CERES‐Maize did not adequately simulate the observed yield reduction under N limitation in our high yielding conditions. Simulations in La Violada watershed indicate that N leaching in maize would still be high (44–98 kg N ha −1 yr −1 ) under an optimized water and N management. Cover crop–maize rotations could reduce N leaching by 31% while supplying similar N availability to maize than fallow–maize rotations. The model was useful to study several management scenarios that would be difficult to investigate under field conditions.